(untitled) (Czech Journal of International Relations, 2004)
Henryk Kierzkowski (ed.): Europe and Globalization. 1st ed. London: Palgrave, 2002, 17 + 332 stran, ISBN 0-333-99839-1 (signatura knihovny ÚMV 49 978).